Plundered Kitchens, Empty Wombs Threatened Reproduction and Identity in the Cameroon Grasslands - Feldman-Savelsberg, Pamela (University of Michigan Press, 1999)
Plundered Kitchens, Empty Wombs examines the symbolic language of food, fertility, and infertility in a small, mountainous African kingdom to explore more general notions of gender, modernity, and cultural identity. In the Cameroon grassfields, an area of high fertility, women hold a paradoxical fear of infertility. By combining symbolic, political-economic, and historical analyses, Pamela Feldman-Savelsberg traces the way reproductive threat is invoked in struggles over gender and ethnic identities. Women's fears of reproductive disorders, she finds, are an important mode of expression for their worries about much larger issues, such as rural poverty, brought about or exacerbated by political and economic changes in this century. A lively case study of an infertile queen who flees the palace sets the stage for discussions of the ethnographic and historical setting, the symbolism of fertility and infertility, and the development and interaction of cosmopolitan and ethno-gynecologies. The book concludes with an analysis of the links between women's role in human reproduction and the divine king's role in social reproduction, both occurring in the rapidly changing context of a multiethnic African nation. Plundered Kitchens, Empty Wombs underscores the relevance of medical anthropology to other anthropological specializations, as well as to epidemiologists, population specialists, and development planners. It should reach a broad audience in medical anthropology, public health, and women's studies.